Gastric microbiota in gastric cancer: Different roles of Helicobacter pylori and other microbes - Guo, Yang; Cao, Xue-Shan; Zhou, Meng-Ge; Yu, Bo (Frontiers in Cellular and Infection Microbiology, 2023)
Gastric cancer (GC) is one of the leading causes of cancer-related deaths worldwide. The gastric microbiota plays a critical role in the development of GC. First, Helicobacter pylori (H. pylori) infection is considered a major risk factor for GC. However, recent studies based on microbiota sequencing technology have found that non-H. pylori microbes also exert effects on gastric carcinogenesis. Following the infection of H. pylori, gastric microbiota dysbiosis could be observed; the stomach is dominated by H. pylori and the abundances of non-H. pylori microbes reduce substantially. Additionally, decreased microbial diversity, alterations in the microbial community structure, negative interactions between H. pylori and other microbes, etc. occur, as well. With the progression of gastric lesions, the number of H. pylori decreases and the number of non-H. pylori microbes increases correspondingly. Notably, H. pylori and non-H. pylori microbes show different roles in different stages of gastric carcinogenesis. In the present mini-review, we provide an overview of the recent findings regarding the role of the gastric microbiota, including the H. pylori and non-H. pylori microbes, in the development of GC.